Assessment of the Concentration of Settleable Particulate Matter Using Geographic Information Systems in the Central Ecuadorian Highlands - Santillán-Lima, Patricio; Rodríguez Llerena, Marco; Santillán-Lima, Juan; Molina-Granja, Fernando; Caichug-Rivera, Daniela; Lozada-Yánez, Raúl (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Pollution is the most obvious factor in the deterioration of environmental quality. This issue affects different media and is closely related to the destructive effects on the environment, the accelerated greenhouse effect, the deterioration of ecosystems, and environmental quality.OBJECTIVES: Determine and characterize the sedimentable particulate matter due to anthropic and natural incidence Using Geographic Information Systems in the Central Ecuadorian Highlands.METHODS: 22 monitoring points were established, these collected sedimentable particulate matter (SPM) through the passive gravimetric method that consists of particulate matter (PM) being deposited by gravity in Petri dishes with filter paper inside for one month. The samples were analyzed and compared with the maximum permissible limits (LMP) of the standards: international (WHO) and national (Agreement 097-A).RESULTS: Showed that all samples comply with the regulations established in Agreement 097-A reformed in 2018 (1 mg / cm2 / month), however, 21 of the 22 samples collected do not comply with WHO regulations being above the maximum permissible limit that is (0.5 mg / cm2 / month), being the SPM a factor that affects air quality in the area.CONCLUSION: A map of concentration and dispersion of the SPM was elaborated with the help of Geographic Information Systems (GIS) where 3 types of ranges to the concentration of the MP were categorized: high, medium, and low, also the areas with the highest degree of concentration of particulate matter were identified, turning out to be the north and south of the study area.
Keywords: Particulate matter (PM); sedimentable particulate matter (SPM); monitoring stations; air pollution